Partial extinction did not diminish spontaneous recovery after 24-hour retention interval - Quintero Felipe, María José; Gutiérrez, María Teresa; Flores Martín, Amanda; Morís Fernández, Joaquín; López-Gutiérrez, Francisco José (My University, 2017)
Fear extinction is not permanent but it may suffer from different forms of relapse. One strategy potentially useful to diminish relapse is the partial extinction treatment, according to which, extinction may be potentiated if a gradual and sparse number of CS-US pairings are introduced within the extinction treatment. The present study, using a differential fear conditioning paradigm, tries to evaluate the efficacy of partial extinction to reduce a specific form of relapse, spontaneous recovery, after a 24 h. retention interval. The results showed that partial extinction did not diminish spontaneous recovery when compared with standard extinction. From a theoretical point of view, the pattern of results found was more consistent with the idea that extinction entails the acquisition of new knowledge than with the idea that there are conditions in which extinction entails the erasure of the original acquisition
Keywords: Memoria; Partial extinction; Relapse